2010
DOI: 10.1007/s00726-010-0571-x
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and integrated stress response in HepG2/C3A cells cultured in amino acid deficient medium

Abstract: The integrated stress response (ISR), a defense mechanism cells employ when under stress (e.g., amino acid deprivation), causes suppression of global protein synthesis along with the paradoxical increased expression of a host of proteins that are useful in combating various stresses. Genes that were similarly differentially expressed under conditions of either leucine- or cysteine-depletion were identified. Many of the genes known to contain an amino acid response element and to be induced in response to eIF2α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 33 publications
5
52
0
Order By: Relevance
“…The amino acid store can also be mobilized by the autophagy-lysosome and ubiquitin-proteasome proteolytic systems (10,11,26), and amino acid starvation potently induces the integrated stress response in various cell models to activate the amino acid transcriptional program (15)(16)(17). However, it remains to be demonstrated whether autophagy differentially regulates the mTORC1 pathway and the integrated stress response.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The amino acid store can also be mobilized by the autophagy-lysosome and ubiquitin-proteasome proteolytic systems (10,11,26), and amino acid starvation potently induces the integrated stress response in various cell models to activate the amino acid transcriptional program (15)(16)(17). However, it remains to be demonstrated whether autophagy differentially regulates the mTORC1 pathway and the integrated stress response.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous studies have shown that ER stress activates autophagy to mitigate cellular stress (19,20), our results revealed that autophagy is required to prevent the integrated stress response. Mammalian cells activate the integrated stress response to cope with various metabolic challenges including amino acid starvation and ER stress, and eIF2a plays a central role in mediating the translational and transcriptional adaptations of this stress response (15)(16)(17). Phosphorylation of eIF2a diminishes general protein translation but paradoxically increases translation of selected mRNA species, including the transcription factor ATF4, which in turn induces the expression of multiple genes involved in amino acid transport and synthesis (18).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations